Improved gas exchange after pneumonectomy in an adult with incomplete pulmonary vein atresia. - van der Werf, T. S. (1994)
Atresia of the pulmonary veins of the left lung and the right upper lobe with moderate pulmonary hypertension was diagnosed in a 20 year old man presenting with exertional dyspnoea and haemoptysis. After left pneumonectomy gas exchange appeared to have improved. This was shown by improved arterial oxygen pressures during all steps of exercise in a cycle ergometer test in comparison with values obtained before surgery. This improvement could be entirely attributed to a decrease in physiological dead space ventilation.